Pembangunan Website Desa Wisata Kalisoka Guna Meningkatkan Daya Saing Pariwisata Kabupaten Tegal - Alfinia Hidayah; Warjiyono - AMIK BSI Tegal (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract - In today's modern era, both personal and organizational use of technology has become a staple in carrying out daily activities. Not only mobile technologies are becoming a trend but information and communication technologies such as the website has become a necessity, especially for companies. Websites that used to be owned by many companies for promotion in developing its business, it has become a necessity to disseminate information for government agencies, educational and pariwisata.Kalisoka is a village located in the administrative region of Tegal, Kalisoka a Tourism Village serving religious tourism and culture , Currently the presence of the Tourism Village Kalisoka not so well known. Hence the need for a website to promote the presence of the expected tourism village is able to increase tourist visits, increase revenues, grow the economy and keep the conservation of the cultural wisdom Kalisoka.Keywords: Website, Tourism, Tourism Village Kalisoka